Simulation Study Towards Productivity Improvement for Assembly Line - Mohamad, Effendi; Salleh, Mohd Rizal (Penerbit Universiti, Universiti Teknikal Malaysia Melaka, 2012)
To compete in an ever growing manufacturing environment, companies have to improve their productivity. This study describes the improvement activities of the ABC Company in Malaysia, using a line balancing technique. With these improvement activities, the company managed to reduce the total time required to complete 600 product units per week, from 256.49 hours down to 208.06 hours, and the lead time from 5 days 7.9 hours down to 4 days 6.8 hours. This study also proposes assembly line improvements, using simulation methods, by focusing on a Material Handling Operator (MHO) solution. A MHO is assigned to a transport box container, from one station in the assembly line to another, so that operators at each workstation can concentrate on their own tasks. Using a process simulation approach, this paper compares the performance of the production model using MHO with that of a production model without MHO. The feasibility of this solution is then discussed.